PERANAN BUDAYA RELIGIUS DAN PEMANFAATAN BUKU SAKU KEBAIKAN TERHADAP KARAKTER ISLAMI SISWA DI SDN RENGASDENGKLOK SELATAN II - Suryadi, Agus (Universitas Negeri Malang, 2024)
Education is really needed by humans as a provision for the life they live both today and in the future. Educational provisions are provided continuously and as early as possible. Religious education is an important foundation for building a person's faith and piety in life as a human being. Therefore, religious education that can be carried out in the community, at home, wherever you are, can of course also be carried out at school. However, currently, moral decline is rife. This is due to a lack of understanding and cultivation of religion. Parents hand over students completely to the school and no longer provide understanding and education in religious values to their children. This moral decline will of course also affect the level of moral and moral decline of a nation which is built on the foundation of the characters of its members. Therefore, it is necessary to instill religious values more seriously, including in schools. The Kindness Pocket Book (BUSAKE) is one of the choices at SDN Rengasdengklok II in an effort to instill religious values with religious habits. This book is used to record the slightest positive things that students do. This book has an impact both on students' environments at school and at home. Pendidikan sangat dibutuhkan oleh manusia sebagai bekal di dalam kehidupan yang dijalani baik hari ini maupun kelak. Pembekalan pendidikan diberikan secara terus menerus dan sedini mungkin. Pendidikan agama menjadi pondasi penting untuk membangun iman dan taqwa seseorang dalam kehidupan sebagai manusia. Oleh karena itu pendidikan agama yang bisa dilaksanakan di masyarakat, di rumah, di manapun berada tentu bisa dilaksanakan juga di sekolah. Namun saat ini, kemerosotan moral sedang marak terjadi. Hal ini dikarenakan kurangnya pemahaman dan penanaman agama. Orang tua menyerahkan siswa sepenuhnya kepada sekolah dan tidak lagi memberikan pemahaman dan pendidikan nilai-nilai agama kepada anak-anaknya. Kemerosotan moral ini tentu saja juga akan mempengaruhi tingkat kemerosotan moral dan akhlak sebuah bangsa yang dibangun dari pondasi karakter-karakter anggotanya. Karena itu, perlu dilakukan penanaman nilai-nilai religius dengan lebih serius, termasuk di sekolah. Buku Saku Kebaikan (BUSAKE) menjadi salah satu pilihan di SDN Rengasdengklok II dalam upaya penananamn nilai-nilai religius dengan pembiasaan keagamaan. Buki ini digunakan untuk mencatat hal-hal positif sekecil apa pun yang dilakukan siswa. Buku ini berdampak baik dalam lingkungan siswa di sekolah maupun di rumah.